Invisible Threat: Kajian Literatur tentang Paparan Mikroplastik dan Implikasinya terhadap Kesehatan Manusia - Rabiatul Adawiyah; Rizky Alviansyah; Khusnun Nadiah; Muhammad Yunus; Dianna Ratnawati (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Microplastics are extremely small plastic particles that have become a major concern in public health and environmental studies. This literature review aims to discuss the sources of microplastics, their routes of exposure to the human body, their distribution in organs, and their potential health impacts. The method used was a literature review of scientific articles and reports published from 2021 onward, retrieved from Google Scholar, PubMed, ScienceDirect, and official websites of organizations such as the WHO, OECD, and the World Bank. The review findings show that microplastics originate from plastic waste, synthetic clothing, cosmetics, vehicle tires, and food packaging. These particles have been detected in blood, lungs, the placenta, feces, and various human tissues, indicating that human exposure is widespread. However, evidence from human studies is still limited, so cause-and-effect relationships cannot yet be confirmed with certainty. Based on these findings, further research is needed to better understand the long-term health effects of microplastics. In addition, efforts to reduce single-use plastics, improve waste management systems, and increase public education are essential to reduce exposure and prevent future health risks.